Mixed Redundancy Strategy for Modular Multilevel Converters in High-Power Applications - Miad Ahmadi; Aditya Shekhar; Pavol Bauer (IEEE Open Journal of the Industrial Electronics Society)
Modular multilevel converters are favorable for efficiently operating high-power usages. The required number of components significantly increases when higher modularity is introduced for the given voltage level, thus reducing the system's reliability. This article suggests a mixed redundancy strategy (MRS) that combines the operational concepts using active and spare redundant submodules. It is shown that more than 50% higher B10 lifetime (the point in time when the system has a 90% probability of survival) is achievable as compared to reliability improvement using fixed-level active redundancy strategy, load-sharing active redundancy strategy, and standby redundancy strategy with the same number of redundant submodules. The tradeoff between operational efficiency and investment cost is explored to define the boundary for selecting the MRS over other redundancy strategies with varying dc-link voltages and average converter loading, considering a ten-year payback period and equivalent B10 lifetime. The change in viability boundary for the MRS is established with increasing B10 lifetime and its sensitivity to power electronic component costs and assumed failure rate. The effect of power capacity with a higher switch current rating is evaluated. Also, the Monte Carlo simulation methodology is proposed to evaluate the practicality and effectiveness of the proposed MRS scheme. Finally, the insights of this study are applied to existing literature.